Interdependence of Ischemic Heart Disease with Diabetes and Hypertension, A Clinically Comparative Study - Omer Aziz Mirza, Malik Faisal Iftekhar, Rizwana Hussain, Hafeez-Ud Din, Arjun Kumar, Muhammad Tahir Ibrahim (Pakistan Journal of Medical & Health Sciences, 2022)
Aims and objectives: The aims and objectives of this study were to raise awareness among persons who have ischemic heart disease and other underlying conditions such as diabetes and hypertension. Methodology: Total 150 individuals of age 50-60 years old were selected for this study. In control group 25 male and 25 females were selected. On the other hand, 75 male and 25 female were in Group-B. All patients of Group-B visited in Cardiology Department of MTI Lady Reading Hospital and Abbottabad International medical college Abbottabad with different cardiac complications like chest pain, high blood pressure, short breathing and sweating etc. Results: In this study different variables were considered and compare these parameters within the group by applying p<0.05 significant regression test. BMI, systolic and diastolic blood pressure, oxygen saturation, intensity of chest pain, smoking habit and random serum glucose levels of both male and female were measured. A significant changes (p<0.05) regarding above parameters in individuals of Group-B were noted as compared with normal individuals of Group-A. Conclusion: In conclusion, there were strong and concrete evidences that diabetes and hypertension are a major risk factors for cardiovascular complications therefore these two metabolic abnormalities were correlated with ischemic illness. There were multiple evidences that structural and biochemical cardiac abnormalities begin in the pre-diabetic state.